2023
DOI: 10.1007/s00423-022-02740-0
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment for pancreatic cystic lesions—implications from the multi-center and prospective German StuDoQ|Pancreas registry

Abstract: Purpose The detection of pancreatic cystic lesions (PCL) causes uncertainty for physicians and patients, and international guidelines are based on low evidence. The extent and perioperative risk of resections of PCL in Germany needs comparison with these guidelines to highlight controversies and derive recommendations. Methods Clinical data of 1137 patients who underwent surgery for PCL between 2014 and 2019 were retrieved from the German StuDoQ|P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…In line with our findings, Henn et al, found a history of pancreatitis in 23% of non-malignant lesions and 19% in malignant lesions. Jaundice and weight loss were significantly more common in patients with malignant lesions, with 10% and 23% reporting these symptoms, respectively 14 . Our results are consistent with Hegazy et al, who reported that abdominal pain was the most common complaint among patients with symptomatic PCLs (13.7%), followed by weight loss (9.8%) and jaundice (7.8%) 15 .…”
Section: Discussionmentioning
confidence: 99%
“…In line with our findings, Henn et al, found a history of pancreatitis in 23% of non-malignant lesions and 19% in malignant lesions. Jaundice and weight loss were significantly more common in patients with malignant lesions, with 10% and 23% reporting these symptoms, respectively 14 . Our results are consistent with Hegazy et al, who reported that abdominal pain was the most common complaint among patients with symptomatic PCLs (13.7%), followed by weight loss (9.8%) and jaundice (7.8%) 15 .…”
Section: Discussionmentioning
confidence: 99%